The Prevention of House Dust Mite Allergies in Pediatric Asthma - Angela Klain; Antonio Andrea Senatore; Amelia Licari; Francesca Galletta; Irene Bettini; Leonardo Tomei; Sara Manti; Francesca Mori; Michele Miraglia del Giudice; Cristiana Indolfi (MDPI AG, 2024)
This review provides a concise overview of preventive measures against dust mite allergies in pediatric populations, emphasizing the need for a comprehensive and evolving approach. Dust mites, ubiquitous microscopic arachnids, pose a significant threat to children's health, triggering allergies and asthma. Traditional preventive strategies such as regular cleaning, mattress covers, and humidity control are essential but warrant refinement. Empowering children through personalized hygiene education and exploring innovative bedding solutions showcase a forward-thinking paradigm. Collaboration with healthcare professionals and embracing technology-driven solutions ensures a holistic and adaptable approach to safeguarding pediatric health against dust mite-related ailments. This abstract underscores the importance of continually reassessing and innovating preventive measures to create resilient and health-conscious living environments for children.